Social networks and family formation processes young adults decision making about parenthood - Keim, Sylvia; SpringerLink (Online Service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
This book is valuable reading for academics, students, and policy makers interested in family research, the network perspective, and mixed-methods research.
Electronic reproduction.
Keywords: Family life education; Electronic books